Anisotropic phantom measurements for quality assured use of diffusion tensor imaging in clinical practice. (June 2013) - Berberat, Jatta; Eberle, Brigitte; Rogers, Susanne; Boxheimer, Larissa; Lutters, Gerd; Merlo, Adrian; Bodis, Stephan; Remonda, Luca
Background: Diffusion-weighted magnetic resonance imaging (MRI) is being increasingly applied in clinical practice, for example in neuronavigation and in modern radiation treatment planning. Quality assurance (QA) is therefore important to avoid clinical errors. Purpose: To compare four analytical programs and a neuronavigation tool to evaluate our in-house diffusion-weighted imaging protocol in order to be able to implement diffusion tensor imaging (DTI) into clinical practice. Material and Methods: A phantom containing crossing fibers was used for the QA. Fiber tracking and fractional anisotropy (FA) analyses were performed, and the geometrical resolution was verified using the phantom. Results: FA results were reproducible within each program and no significant differences between programs were observed. Also, no significant differences in FA values were found when comparing the results between the four software programs. Geometrical resolution of the anatomical data-set was satisfactory; however the crossing of the fibers was not accurately represented by three of the four programs. Conclusion: Phantom QA is necessary before using DTI for novel procedures to identify the uncertainties associated with DTI data. It is important to remember that the results are software-dependent and that representation of the tracts may vary between software products. We therefore recommend caution with regard to the application of fiber tracking results intraoperatively when dealing with abnormal fiber tract anatomy.